(untitled) (Scientific journal of the Fergana State University, 2023)
The article highlights that the feeding of imported heifers with rapeseed (colza) flour used as forage crops in the amount of 15% of the protein content in the ration had a positive effect on metabolic processes and led to an intensive average daily gain in live weight.